2008
DOI: 10.17221/1963-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dehydroepiandrosterone on growth performance, lipid metabolic hormones and parameters in broilers

Abstract: ABSTRACT:One hundred and eighty (180) day-old broiler chickens were used to investigate the effects of dehydroepiandrosterone (DHEA) on growth performance, carcass composition, and the serum concentrations of several lipid metabolic hormones and metabolic parameters (indicators). The broilers received the same basal diets, with DHEA added at 0 (control), 5 and 20 mg/kg feed. During the experimental period, broilers fed DHEA exhibited lower levels of triglycerides (TG), total serum cholesterol (TC), high densit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
2
3
0
Order By: Relevance
“…This observation in in line with previous studies, which reported that DHEA administration reduce body weight gain (Shepherd and Cleary, 1984;Cleary and Zisk, 1986;Cleary, 1991;Svec et al, 1995;Abadie et al, 2000;Zhao et al, 2007;Ma et al, 2008;Hakkak et al, 2010Hakkak et al, & 2017. The decrease in body weight gain may be related to the decrease in food intake (Weindruch et al, 1984), or related to the decrease the abdominal or body fats (Cleary and Zisk, 1986;Villareal and Holloszy, 2004;Ma et al, 2008). However, other studies reported that DHEA treatment causes a decrease in the body weight (Tagliaferro et al, 1986;Mohan et al, 1990;Yamada et al, 1991;Han et al, 1998;Ng et al, 1999;Richards et al, 2000;Kopplow et al, 2005;de Heredia et al, 2007;Caldwell et al, 2014;Chen et al, 2015), and other studies found no effect for DHEA on body weight (Lea-Currie et al, 1997 a, b;Aragno et al, 2004;Sander et al, 2006;Miyazaki et al, 2016).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This observation in in line with previous studies, which reported that DHEA administration reduce body weight gain (Shepherd and Cleary, 1984;Cleary and Zisk, 1986;Cleary, 1991;Svec et al, 1995;Abadie et al, 2000;Zhao et al, 2007;Ma et al, 2008;Hakkak et al, 2010Hakkak et al, & 2017. The decrease in body weight gain may be related to the decrease in food intake (Weindruch et al, 1984), or related to the decrease the abdominal or body fats (Cleary and Zisk, 1986;Villareal and Holloszy, 2004;Ma et al, 2008). However, other studies reported that DHEA treatment causes a decrease in the body weight (Tagliaferro et al, 1986;Mohan et al, 1990;Yamada et al, 1991;Han et al, 1998;Ng et al, 1999;Richards et al, 2000;Kopplow et al, 2005;de Heredia et al, 2007;Caldwell et al, 2014;Chen et al, 2015), and other studies found no effect for DHEA on body weight (Lea-Currie et al, 1997 a, b;Aragno et al, 2004;Sander et al, 2006;Miyazaki et al, 2016).…”
Section: Discussionsupporting
confidence: 93%
“…The decrease in body weight gain was dose-dependent. This observation in in line with previous studies, which reported that DHEA administration reduce body weight gain (Shepherd and Cleary, 1984;Cleary and Zisk, 1986;Cleary, 1991;Svec et al, 1995;Abadie et al, 2000;Zhao et al, 2007;Ma et al, 2008;Hakkak et al, 2010Hakkak et al, & 2017. The decrease in body weight gain may be related to the decrease in food intake (Weindruch et al, 1984), or related to the decrease the abdominal or body fats (Cleary and Zisk, 1986;Villareal and Holloszy, 2004;Ma et al, 2008).…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies have shown that adding antimicrobial peptides to feed can improve animal serum indicators ( 32 , 33 ). It found that adding 100 mg/kg antimicrobial peptide to the Luhua chicken diet could significantly increase the serum total protein content at 42 and 70 days of age and improve the albumin content, consistent with our study ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…It found that adding 100 mg/kg antimicrobial peptide to the Luhua chicken diet could significantly increase the serum total protein content at 42 and 70 days of age and improve the albumin content, consistent with our study ( 34 ). Furthermore, adding 100 mg/kg antimicrobial peptide could increase the levels of IgG and IgM in broilers at 35 days of age ( 32 ). Moreover, it also found that SGAMP increased IgA levels in broiler serum ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the poultry industry, the production of broiler chickens with excessive body fat is currently seen as a significant economic problem (Ma et al, 2008). The deposition of abdominal fat in broilers results in increased feed cost and poor final meat quality (Assaf et al, 2004).…”
Section: Introductionmentioning
confidence: 99%